Masculinities and health care in aging and health-illness process among male workers from Campinas/São Paulo, Brazil - Separavich, Marco Antonio; Canesqui, Ana Maria (Saúde e Sociedade, 2020)
This article discusses gender, health, illness and masculinity anchored in the social markers of identity that endorse the diversity of masculinity regarding social behavior and health care. This is a qualitative study with 15 men from the low income working class living in Campinas, São Paulo. It focuses on the social representation about health and illness as well as aging and health care. Strength andwillingness toworkwere associatedwith health and dominant masculinity, in contrast to illness and unwillingness to work. Aging involves the effect ofthe time on body wear, bodily fragilities, and their position regarding life and old age. This last concept does not derive from chronological age, but from the perceptions of identity. Healthcare is concerned with successful aging, which endorsed by some men who tend to not preserve the dominant masculinity, a fact of which is associated to the major better caring about health.